Everolimus in Invasive Malignant Renal Epithelioid Angiomyolipoma - Guo, Gang; Gu, Liangyou; Zhang, Xu (Frontiers in Oncology, 2021)
Background To evaluate the efficacy and safety of everolimus, a mTOR inhibitor, on invasive malignant renal epithelioid angiomyolipoma (EAML). Materials and Methods From Oct 2014 to May 2019, we collected data from seven patients with a definite (clinical and pathological) diagnosis of EAML received everolimus in our hospital. Targeted sequence capture array technique with next-generation of high throughput sequencing (NGS) were performed to detect mutations of TSC1/2 genes. All patients had received surgery and everolimus. The clinical efficacy and safety of the therapy were evaluated. Results Mutations of TSC1 and TSC2 were detected in two and three patients though targeted sequence capture array technique with NGS, respectively. Among seven patients, three had missense mutations, one had nonsense mutation, and one had the large fragment deletion mutation. Five patients accompanied with tuberous sclerosis complex (TSC) were identified. All patients were administered 10mg everolimus once daily, the treatment duration lasted for 3 to 28 months. The objective response was assessed 3 months later, five partial response, two stable disease (SD), the mean greatest tumor diameter of all patients decreased from 9.6 to 5.2cm. Six patients stayed SD and one patient died during follow up. Patients accompanying with TSC had better responses to everolimus compared with non-TSC. Conclusion The mTOR inhibitor can be an effective treatment for patients with invasive malignant renal EAML. Patients with TSC may benefit more from the therapy.